The effect of lyrical and non-lyrical background music on different types of language processing - An ERP study - Eun Kyoung Lee(이은경); Sung Eun Lee(이성은); Young Sung Kwon(권영성) (인지과학, 2020)
People read in different settings, including when music is playing in the background. Whether the presence of music facilitates, hinders, or does not affect language processing is an on-going debate in the current literature. The present study used ERPs to examine the influence of music on orthographic, semantic, and syntactic processing by inspecting P2, N400, and P600 responses, respectively. A total of 60 participants judged the correctness of visually presented sentences while listening to music with lyrics, music without lyrics, or in silence. The results showed that the P2 and P600 effects were larger in the silent condition than in the music-with-lyrics condition, while there were no N400 differences among the conditions. This indicates that only lyrical music interferes with orthographic and syntactic language processing, while it has no, or minimal, effect on semantic processing. The results are discussed in relation to the background music interference effect. KCI Citation Count: 0